Effect of Supplementing Azolla microphylla on Feed Intake and Blood Parameters in Growing Crossbred Female Calves - Khare, Arbind; Chatterjee, A.; Mondal, M.; Karunakaran, M.; Ghosh, M.K.; Dutta, T.K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted on 12 crossbred female calves distributed into two groups to assess the effect of supplementing Azolla microphylla on feed intake and blood parameters. The animals in group T0 were fed with conventional ration consisting of paddy straw and concentrate mixture in 1: 1 ratio. In group T1, fresh Azolla microphylla was supplemented @ 1.5 kg/animal (equivalent to 90 g DM) replacing equivalent weight of concentrate mixture on DM basis. The feed intake was similar in both the groups, however, growth rate was better (P<0.01) in group T1. No significant differences were observed with regard to Hb, RBC, WBC, glucose, NEFA, a-amino nitrogen, urea N, total protein, albumin, ALT and AST between the two groups. The concentration of GH, T3, T4 and leptin was also similar in two groups. Therefore, supplementation of Azolla microphylla @ 1.5 kg/day/animal on fresh basis did not affect feed intake, the levels of blood metabolites, haematological indices and hormones in crossbred growing heifers showing no adverse effect on health.